Spirituality and Anxiety in Nursing Students of Faculty of Nursing and Midwifery Iran University of Medical Science -2006 - Tahereh Ganji; Agh Fatemeh Hosseini (Iran University of Medical Sciences, 2010)
Background and Aim: Anxiety is a widespread human phenomenon accompanying the painful expectation of an undesirable event (1), and it's a common response to tension, an unpleasant mental situation.   Stress and anxiety would result in hopelessness, lacking power, proficiency and control over life.   We can reduce the affects of anxiety by applying some methods. The research results, as an example, showed that we can reduce the negative affects of anxiety through increasing the religious beliefs, and generally there is a strong relation between people's religious beliefs and their health.   The purpose of this study was to determine the relation between spirituality and level of anxiety in nursing students of Faculty of Nursing and Midwifery Iran University of Medical Science 2005-2006.   Material and Methods: the research society was all of the students of Faculty of Nursing and Midwifery Iran University of Medical Science who were studying in the Faculty of Nursing and Midwifery Iran University of Medical Science at the time of this research.   Among them 108 students were selected by chance. We had 3 questionnaires for data collection. The first was concerned with personal characteristics. The second was concerned with the spirituality and. Third questionnaire was anxiety scale.   Results: finding have shown that most of samples had highly spirituality (76.9%).consequently there was a meaningful relation between spirituality and religious activities (P = 0.000).   Resultswere indicating that 51.9% of samples had no anxiety (mean ± 12.86 ± 10.87).   There was a meaningful statistical relation between anxiety and crisis experience within the last 6 months (P = 0.001).   Concerning the relation between spirituality and level of anxiety. Spearman's test showed that the higher the level of spirituality, the lower the level of anxiety (r = -0.398, P = 0.001). as a result, the hypothesis was accepted.